Previous hip surgery due to developmental dysplasia of the hip affects major complication rates but not revision rates in total hip arthroplasty (Annals of Medical Research, 2021)
Aim: Total hip arthroplasty in patients with developmental dysplasia of the hip is challenging due to accompanying acetabular and femoral deformities, soft-tissue contractures and shortening of the affected limb. In addition, changed anatomy after pelvic and/or femoral osteotomies can also make the total hip arthroplasty procedure challenging. This study aimed to evaluate the effect of previous hip surgery on clinical and radiological outcomes after total hip arthroplasty in previously operated patients due to developmental dysplasia of the hip. Material and Methods: A total of 55 developmental dysplasia of the hip patients, twenty-five patients (29 hips) with a previous hip surgery (Group 1) and 30 patients (31 hips) without previous hip surgery (Group 2) were included. The primary outcome measures were major complication and revision rates. The secondary outcome measure was the Harris Hip Score.Results: Major complications were found significantly higher in group I (p = 0.009). However, no significant difference was observed between groups regarding revision rates (p = 0.514). No significant difference was observed between groups in the preoperative and the last follow-up Harris Hip scores.Conclusion: Although similar revision rates, patients with a previous hip surgery due to developmental dysplasia of the hip who underwent total hip arthroplasty are more prone to major complications than patients without previous hip surgery patients. Level of Evidence IV. Case-Control Study.
Keywords: Developmental dysplasia of the hip; major complication; osteotomy; revision; total hip arthroplasty